THE RISK OF DECREASED COGNITIVE EFFORT IN LEARNERS (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This study examines the impact of decreased cognitive effort among learners on educational effectiveness and instructional design. It emphasizes the importance of optimizing cognitive load and implementing active learning strategies that promote deeper engagement and understanding. The active learning approach, unlike traditional passive methods, positively influences learners’ cognitive, motivational, and emotional self-regulatory processes. However, the study highlights the need for educators to balance cognitive challenges to prevent overload, which can hinder comprehension and knowledge retention. Furthermore, integrating technology within the Technological Pedagogical Content Knowledge (TPACK) framework is proposed as a means to enhance cognitive engagement and transform learning experiences. The research also underscores the importance of addressing behavioral issues through positive behavioral interventions to promote inclusivity and equitable learning outcomes. Overall, the findings contribute to a better understanding of how thoughtful instructional design and balanced cognitive demands can foster deeper learning and prepare students for complex problem-solving in the 21st century.